Size and receptor density of glutamatergic synapses: a viewpoint from left-right asymmetry of CA3-CA1 connections - Shinohara, Yoshiaki; Hirase, Hajime (Frontiers in Neuroanatomy, 2009)
Synaptic plasticity is considered to be the main mechanism for learning and memory. Excitatory synapses in the cerebral cortex and hippocampus undergo plastic changes during development and in response to electric stimulation. It is widely accepted that this process is mediated by insertion and elimination of various glutamate receptors. In a series of recent investigations on left-right asymmetry of hippocampal CA3-CA1 synapses, glutamate receptor subunits have been found to have distinctive expression patterns that depend on the postsynaptic density (PSD) area. Particularly notable are the GluR1 AMPA receptor subunit and NR2B NMDA receptor subunit, where receptor density has either a supra-linear (GluR1 AMPA) or inverse (NR2B NMDAR) relationship to the PSD area. We review current understanding of structural and physiological synaptic plasticity and propose a scheme to classify receptor subtypes by their expression pattern with respect to PSD area.